MENINGKATKAN HASIL BELAJAR PESERTA DIDIK MELALUI MEDIA PEMBELAJARAN APLIKASI WORDWALL MATA PELAJARAN PENDIDIKAN PANCASILA KELAS V SD NEGERI 241 PALEMBANG - Hervindri Indar Ningsih; Yenny Anwar; Nur Fitra Dewi (JOURNAL SAINS STUDENT RESEARCH, 2025)
The use of learning media is a very important factor to improve learning outcomes and learner motivation in learning. Wordwall is an application-based learning media that can be used as a learning medium that is easy to use and is able to improve the results of the learners' abilities. The purpose of this research is to improve the learning outcomes of students. The subjects in this study are students in class V of SD Negeri 241 Palembang which totals 28 students, divided into 13 boys and 15 girls. This type of research is a class action research with two cycles, the data collection technique used is observation and learning results test in the form of an evaluation sheet. Based on the research results, a completion percentage of 54% was obtained with 15 students in cycle I while cycle II obtained a completion percentage of 89% with 25 students. So it can be concluded that the learning results of students have improved after applying the wordwall application media in Pancasila Education subjects.